Making sense of overconfidence in market entry. (8th November 2013) - Cain, Daylian M.; Moore, Don A.; Haran, Uriel
<x xml:space="preserve">Abstract</x> Entrepreneurs are often described as overconfident (or at least very confident), even when entering difficult markets. However, recent laboratory findings suggest that difficult tasks tend to produce underconfidence. How do entrepreneurs maintain confidence in difficult tasks? Our two laboratory experiments and one archival study reconcile the literature by distinguishing types of overconfidence and identifying what type is most prominent in each type of task. Furthermore, we critically examine the notion that 'overconfidence' explains excess market entry: we find that entry into different markets is not driven by confidence in one's own absolute skill, but by confidence in one's skill relative to that of others. Finally, we consider whether overconfidence in relative skill is driven by neglecting competitors or by systematic errors made when considering them. Copyright © 2013 John Wiley & Sons, Ltd.